Fermented foods as a strategy to reduce heavy metal toxicity in humans: Mechanistic insights and emerging evidence - Ramak Esfandi; Julia Farrell Lacika; Raymond Thomas; Jeremy P. Burton; Carla Liria Sánchez-Lafuente (Trends in Food Science & Technology, 2026)

Floodplain-lake hydroperiod modulates the response of zooplankton and phytoplankton resting stages to extreme droughts - G. Chaparro; I. O’Farrell; N. S. Morandeira; M. P. Gayol (Hydrobiologia, 2026)

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Hydrodynamic and sedimentary processes in sedimentation fields: the requirement for continued maintenance to preserve restored intertidal habitat - Jonathan Dale; Cai J.T. Ladd; Michelle Farrell; Michael P. Kennedy; Gabriela Ciappara; Chloe James; Iain Fairley (Journal of Environmental Management, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Peatland use and peat soil land cover types in Ireland: Implications for the calculation of GHG emissions in the context of climate action - L. Gilet; W. Habib; E. Aitova; K.A. Byrne; C.A. Farrell; O. Fenton; R. Flynn; D. O’Leary; T.R. Morley; P. Tuohy; S. Regan; F. Renou-Wilson; et al. (Land Use Policy, 2025)

Fracture analysis of the lithium-bearing Cligga Head granite: Impacts on critical mineral mobilisation and fluid flow - Andrew J.M. Evans; Natalie J.C. Farrell; David A. Neave; Margaret E. Hartley; David Healy; John P. Waters; Tara R. McElhinney; Joshua J. Shea; Nico Bigaroni; Simon A. Hunt (Journal of Structural Geology, 2025)

Quantifying Benthic Flux of Mysis Biomass Through Diel Vertical Migration at the Ecosystem Scale - Brian P. O’Malley; Georgia W. Hoffman; Rosaura J. Chapina; Jason D. Stockwell; Collin J. Farrell (Ecosystems, 2025)
Mysis diluviana is a macroinvertebrate that couples benthic and pelagic habitats on a daily timescale through diel vertical migration (DVM). However, quantifying how much Mysis biomass is exchanged between benthic and pelagic habitats at an ecosystem scale is difficult because of sampling limitations and variability in Mysis DVM behavior related to light and depth. Although Mysis are benthic-pelagic migrators, a portion remains pelagic during the day offshore in Lake Ontario, partially contradicting the assumption of population-level DVM over deep areas. To estimate the amount of biomass transferred from benthic to pelagic habitat via DVM in Lake Ontario, we estimated the portion of pelagic biomass at night originating from benthic habitat as the difference between night and day pelagic estimates from net tows along a bathymetric depth gradient. We then modeled the portion as a function of depth, extrapolated these depth-dependent estimates to an existing lake wide night-pelagic dataset, and summed amounts across depth strata. We estimated more biomass was transferred from benthic to pelagic habitat at intermediate lake depths (100–160 m) despite greater offshore (> 180 m) night-pelagic biomass. Our results suggest ways to improve estimates of Mysis habitat coupling and how to account for important factors such as depth and light for modeling Mysis DVM behavior at the population- and ecosystem-levels.

On the equatorial dayside ionosphere of Saturn – In-situ observations give evidence for a dynamic and layered structure in disequilibrium - J.-E. Wahlund; A.I. Eriksson; M.W. Morooka; S. Buchert; M. Persson; E. Vigren; J. Dreyer; W.S. Kurth; J.H. Jr Waite; J.-P. Lebreton; W.M. Farrell; I. Müller-Wodarg (Icarus, 2025)

Microbial community response to spent mushroom substrate composting methods by phospholipid fatty acid analysis - Siobhan N. Jordan; Michael P. Farrell; Caroline T. Gilleran Stephens (Biocatalysis and Agricultural Biotechnology, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

Antimicrobial resistant Enterobacterales of clinical importance in mute swans - Aneta Kovarova; Graham Prole; Maeve Louise Farrell; Mark Maguire; Louise Catherine Murphy; Alexandra Chueiri; Louise O'Connor; Georgios Miliotis; Dearbháile Morris; Liam P. Burke (Science of The Total Environment, 2025)

A genome assembly and transcriptome atlas of the inbred Babraham pig to illuminate porcine immunogenetic variation - John C. Schwartz; Colin P. Farrell; Graham Freimanis; Andrew K. Sewell; John D. Phillips; John A. Hammond (Immunogenetics, 2024)
The inbred Babraham pig serves as a valuable biomedical model for research due to its high level of homozygosity, including in the major histocompatibility complex (MHC) loci and likely other important immune-related gene complexes, which are generally highly diverse in outbred populations. As the ability to control for this diversity using inbred organisms is of great utility, we sought to improve this resource by generating a long-read whole genome assembly and transcriptome atlas of a Babraham pig. The genome was de novo assembled using PacBio long reads and error-corrected using Illumina short reads. Assembled contigs were then mapped to the porcine reference assembly, Sscrofa11.1, to generate chromosome-level scaffolds. The resulting TPI_Babraham_pig_v1 assembly is nearly as contiguous as Sscrofa11.1 with a contig N50 of 34.95 Mb and contig L50 of 23. The remaining sequence gaps are generally the result of poor assembly across large and highly repetitive regions such as the centromeres and tandemly duplicated gene families, including immune-related gene complexes, that often vary in gene content between haplotypes. We also further confirm homozygosity across the Babraham MHC and characterize the allele content and tissue expression of several other immune-related gene complexes, including the antibody and T cell receptor loci, the natural killer complex, and the leukocyte receptor complex. The Babraham pig genome assembly provides an alternate highly contiguous porcine genome assembly as a resource for the livestock genomics community. The assembly will also aid biomedical and veterinary research that utilizes this animal model such as when controlling for genetic variation is critical.

Impacts of Fulvic Acid on the Toxicity of the Herbicide Atrazine to Lemna minor - P. Chris Wilson; Francisca O. Hinz; Ilana Farrell (Bulletin of Environmental Contamination and Toxicology, 2024)

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Longitudinal carriage of antimicrobial resistant Enterobacterales in healthy individuals in Ireland - Assessing the impact of recreational water use on duration of carriage - Maeve Louise Farrell; Alexandra Chueiri; Mark Maguire; Aneta Kovářová; Georgios Miliotis; Louise O'Connor; Francesca McDonagh; Sinead Duane; Martin Cormican; Genevieve Devane; Alma Tuohy; Niall DeLappe; et al. (Science of The Total Environment, 2023)

Flow induced attrition of cellulose nanocrystals - Bradley P. Sutliff; Connor Farrell; Stephen M. Martin; Michael J. Bortner (Carbohydrate Polymers, 2023)

Assessing the impact of recreational water use on carriage of antimicrobial resistant organisms - Maeve Louise Farrell; Alexandra Chueiri; Louise O'Connor; Sinead Duane; Mark Maguire; Georgios Miliotis; Martin Cormican; Brigid Hooban; Anne Leonard; William H. Gaze; Genevieve Devane; Alma Tuohy; et al. (Science of The Total Environment, 2023)

Endurance Swimming Is Related to Summer Lake Survival of Rainbow Trout in a Warm Lake with Avian Piscivores - Christine E. Verhille; Anthony P. Farrell (Fishes, 2023)
Fitness of fish is assumed to be influenced by locomotion performance, but empirical evidence linking swimming capacity to survival in nature remains sparse. Poor triploid (3N) fish aerobic swimming performance in conjunction with production of sibling diploid (2N) and 3N populations of genetically identical origin to minimize variability among compared populations make 3N trout an informative system to test hypotheses about fitness consequences of fish locomotion. Here, we ask if reduced survival of 3N relative to 2N trout in natural ecosystems during periods of high temperature relate to a lower aerobic swimming capacity and aerobic scope of 3N compared with 2N conspecifics. Three-yearly cohorts of conspecific 2N and 3N hatchery-reared, yearling rainbow trout were ranked for swimming endurance, externally marked for their endurance quantile, and then stocked into two lakes as yearlings to quantify their survival in the wild over summer as a function of ploidy, temperature and endurance; all while tracking temperature and depth habitat utilization via telemetry. As expected, 3N swimming endurance was lower than that of 2N, but with considerable individual overlap. Aerobic swimming endurance, especially for 3N, was predictive of summer survival in a warm lake where piscivorous birds potentially exerted high predation pressure, resulting in low fish survival. This empirical evidence of a connection between swimming endurance and fitness provides support for long held assumptions of this relationship and could inform future sport fishing stocking industry practices to match fish strains to ideal habitats.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Testing the hypoxia tolerance and hypoxic performance of fishes: A two-tier screening approach - Yangfan Zhang; Anthony P. Farrell (Frontiers in Marine Science, 2022)
With regional hypoxic episodes in the world’s oceans becoming more severe and more frequent, a valuable management need will be a screening protocol to characterize the full diversity of hypoxic robustness among fishes (defined here as their tolerance and performance). Yet, high-throughput screening protocols to deal with the almost 33,000 fish species have the potential to trade off convenience with the information depth normally provided with comprehensive but more time-consuming phenotyping protocols. As a solution, we propose a two-tier testing approach, one that combines a simple, rapid, cost-effective, and well-established hypoxia challenge test (a measure of hypoxic tolerance) with an individual-based hypoxic performance test that defines maximum aerobic capacity over a wide range of ambient water oxygen levels (a hypoxic performance curve). The later test would be performed on selected indicator species identified from the tolerance screening test. Here we describe the two methodological approaches for this two-tier approach using some existing data to illustrate the potential for their applications in marine science.

Stable carbon and nitrogen isotopes explain methylmercury concentrations in stream food webs of Lake George, New York (USA) - M. W. Swinton; P. K. Myer; M. F. Schaller; E. A. Pettitt; J. L. Farrell; S. A. Nierzwicki-Bauer (Ecotoxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Year-round acoustic monitoring of Antarctic blue and fin whales in relation to environmental conditions off the west coast of South Africa - Ishmail S. Letsheleha; Fannie W. Shabangu; Dara Farrell; Rex K. Andrew; Philip L. la Grange; Ken P. Findlay (Marine Biology, 2022)

Host‐pathogen‐environment interactions predict survival outcomes of adult sockeye salmon ( Oncorhynchus nerka ) released from fisheries - Amy K. Teffer; Scott G. Hinch; Kristina M. Miller; David. A. Patterson; Arthur L. Bass; Steven J. Cooke; Anthony P. Farrell; Terry D. Beacham; Jacqueline M. Chapman; Francis Juanes (Molecular Ecology, 2022)
Incorporating host‐pathogen(s)‐environment axes into management and conservation planning is critical to preserving species in a warming climate. However, the role pathogens play in host stress resilience remains largely unexplored in wild animal populations. We experimentally characterized how independent and cumulative stressors (fisheries handling, high water temperature) and natural infections affected the health and longevity of released wild adult sockeye salmon ( Oncorhynchus nerka ) in British Columbia, Canada. Returning adults were collected before and after entering the Fraser River, yielding marine‐ and river‐collected groups, respectively ( N = 185). Fish were exposed to a mild (seine) or severe (gill net) fishery treatment at collection, and then held in flow‐through freshwater tanks for up to four weeks at historical (14°C) or projected migration temperatures (18°C). Using weekly nonlethal gill biopsies and high‐throughput qPCR, we quantified loads of up to 46 pathogens with host stress and immune gene expression. Marine‐collected fish had less severe infections than river‐collected fish, a short migration distance (100 km, 5–7 days) that produced profound infection differences. At 14°C, river‐collected fish survived 1–2 weeks less than marine‐collected fish. All fish held at 18°C died within 4 weeks unless they experienced minimal handling. Gene expression correlated with infections in river‐collected fish, while marine‐collected fish were more stressor‐responsive. Cumulative stressors were detrimental regardless of infections or collection location, probably due to extreme physiological disturbance. Because river‐derived infections correlated with single stressor responses, river entry probably decreases stressor resilience of adult salmon by altering both physiology and pathogen burdens, which redirect host responses toward disease resistance.

Effects of global warming on fishes and fisheries - David J. McKenzie; Benjamin Geffroy; Anthony P. Farrell (Journal of Fish Biology, 2021)

Intraspecific variation in tolerance of warming in fishes - David J. McKenzie; Yangfan Zhang; Erika J. Eliason; Patricia M. Schulte; Guy Claireaux; Felipe R. Blasco; Julie J.H Nati; Anthony P. Farrell (Journal of Fish Biology, 2021)
Intraspecific variation in key traits such as tolerance of warming can have profound effects on ecological and evolutionary processes, notably responses to climate change. The empirical evidence for three primary elements of intraspecific variation in tolerance of warming in fishes is reviewed. The first is purely mechanistic that tolerance varies across life stages and as fishes become mature. The limited evidence indicates strongly that this is the case, possibly because of universal physiological principles. The second is intraspecific variation that is because of phenotypic plasticity, also a mechanistic phenomenon that buffers individuals’ sensitivity to negative impacts of global warming in their lifetime, or to some extent through epigenetic effects over successive generations. Although the evidence for plasticity in tolerance to warming is extensive, more work is required to understand underlying mechanisms and to reveal whether there are general patterns. The third element is intraspecific variation based on heritable genetic differences in tolerance, which underlies local adaptation and may define long‐term adaptability of a species in the face of ongoing global change. There is clear evidence of local adaptation and some evidence of heritability of tolerance to warming, but the knowledge base is limited with detailed information for only a few model or emblematic species. There is also strong evidence of structured variation in tolerance of warming within species, which may have ecological and evolutionary significance irrespective of whether it reflects plasticity or adaptation. Although the overwhelming consensus is that having broader intraspecific variation in tolerance should reduce species vulnerability to impacts of global warming, there are no sufficient data on fishes to provide insights into particular mechanisms by which this may occur.

Valid oxygen uptake measurements: using high r 2 values with good intentions can bias upward the determination of standard metabolic rate - Denis Chabot; Yangfan Zhang; Anthony P. Farrell (Journal of Fish Biology, 2021)
This analysis shows good intentions in the selection of valid and precise oxygen uptake ( O 2 ) measurements by retaining only slopes of declining dissolved oxygen level in a respirometer that have very high values of the coefficient of determination, r 2 , are not always successful at excluding nonlinear slopes. Much worse, by potentially removing linear slopes that have low r 2 only because of a low signal‐to‐noise ratio, this procedure can overestimate the calculation of standard metabolic rate (SMR) of the fish. To remedy this possibility, a few simple diagnostic tools are demonstrated to assess the appropriateness of a given minimum acceptable r 2 , such as calculating the proportion of rejected O 2 determinations, producing a histogram of the r 2 values and a plot of r 2 as a function of O 2 . The authors offer solutions for cases when many linear slopes have low r 2 . The least satisfactory but easiest to implement is lowering the minimum acceptable r 2 . More satisfactory solutions involve processing (smoothing) the raw signal of dissolved oxygen as a function of time to improve the signal‐to‐noise ratio and the r 2 s.

Strong effects of a mutualism on freshwater community structure - Robert P. Creed; James Skelton; Kaitlin J. Farrell; Bryan L. Brown (Ecology, 2021)
Numerous mutualisms have been described from terrestrial and marine communities and many of these mutualisms have significant effects on community structure and function. In contrast, there are far fewer examples of mutualisms from freshwater habitats and there is no evidence that any mutualism has community‐wide or ecosystem‐level consequences. Northern hemisphere crayfish are host to a variety of ectosymbiotic worms called branchiobdellidans. The association between some of these “crayfish worms” and their hosts is a mutualism. The outcome of the association is context dependent and can be influenced by host size, symbiont number, and the environment. Here we document in two experiments that the mutualism between crayfish and these worms alters the effect of crayfish on stream community structure and sediment deposition, an important ecosystem variable. We enclosed crayfish stocked with 0 worms and intermediate (3–6) and high worm densities (12) in cages in streams in Boone, North Carolina and Clemson, South Carolina, United States. At both locations, there was a negative relationship between initial worm density and final macroinvertebrate abundance. There was a significant effect of worm treatment on macroinvertebrate community structure in both the Boone and Clemson experiments. In Boone, there were effects on both overall macroinvertebrate abundance and community composition, whereas in Clemson, changes to community structure were primarily driven by changes in total abundance. There was a negative relationship between benthic sediment volume and initial worm density in both experiments, primarily later in the experiments, though these effects were influenced by sediment deposition rates. Our results are the first to demonstrate strong effects of a mutualism on freshwater communities. Both members of this mutualism are found throughout the northern hemisphere, so similar impacts may occur in many other waterways. Given that various species in addition to crayfish function as keystone species and ecosystem engineers in freshwater systems throughout the world, mutualisms involving these strongly interacting species may be as important to the structure and functioning of freshwater systems as comparable mutualisms in marine and terrestrial systems.

Differential effects of bicarbonate on severe hypoxia- and hypercapnia-induced cardiac malfunctions in diverse fish species - Mandy Lo; Arash Shahriari; Jinae N. Roa; Martin Tresguerres; Anthony P. Farrell (Journal of Comparative Physiology B, 2021)

The effect of temperature acclimation on the force-frequency relationship and adrenergic sensitivity of the ventricle of two populations of juvenile sockeye salmon - A. T. Goulding; A. P. Farrell (Journal of Comparative Physiology B, 2020)

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

Measuring maximum oxygen uptake with an incremental swimming test and by chasing rainbow trout to exhaustion inside a respirometry chamber yields the same results - Yangfan Zhang; Matthew J. H. Gilbert; Anthony P. Farrell (Journal of Fish Biology, 2020)
This study hypothesized that oxygen uptake ( Ṁ O 2 ) measured with a novel protocol of chasing rainbow trout Oncorhynchus mykiss to exhaustion inside a static respirometer while simultaneously monitoring Ṁ O 2 ( Ṁ O 2chase ) would generate the same and repeatable peak value as when peak active Ṁ O 2 ( Ṁ O 2active ) is measured in a critical swimming speed protocol. To reliably determine peak Ṁ O 2chase , and compare to the peak during recovery of Ṁ O 2 after a conventional chase protocol outside the respirometer ( Ṁ O 2rec ), this study applied an iterative algorithm and a minimum sampling window duration ( i.e. , 1 min based on an analysis of the variance in background and exercise Ṁ O 2 ) to account for Ṁ O 2 dynamics. In support of this hypothesis, peak Ṁ O 2active (707 ± 33 mg O 2 h −1 kg −1 ) and peak Ṁ O 2chase (663 ± 43 mg O 2 h −1 kg −1 ) were similar ( P = 0.49) and repeatable (Pearson's and Spearman's correlation test; r ≥ 0.77; P Ṁ O 2max can be independent of whether a fish is exhaustively chased inside a respirometer or swum to fatigue in a swim tunnel, provided Ṁ O 2 is analysed with an iterative algorithm and a minimum but reliable sampling window. The importance of using this analytical approach was illustrated by peak Ṁ O 2chase being 23% higher ( P P Ṁ O 2chase was 18% higher ( P Ṁ O 2rec , chasing a fish inside a static respirometer may be a better protocol for obtaining maximum Ṁ O 2 .

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)

The effect of acute warming and thermal acclimation on maximum heart rate of the common killifish Fundulus heteroclitus - Hamid Safi; Yangfan Zhang; Patricia M. Schulte; Anthony P. Farrell (Journal of Fish Biology, 2019)
Common killifish Fundulus heteroclitus were acclimated to ecologically relevant temperatures (5, 15 and 33°C) and their maximum heart rate ( f Hmax ) was measured at each acclimation temperature during an acute warming protocol. Acclimation to 33°C increased peak f Hmax by up to 32% and allowed the heart to beat rhythmically at a temperature 10°C higher when compared with acclimation to 5°C. Independent of acclimation temperature, peak f Hmax occurred about 3°C cooler than the temperature that first produced cardiac arrhythmias. Thus, when compared with previously published values for the critical thermal maximum of F. heteroclitus , the temperature for peak f Hmax was cooler and the temperature that first produced cardiac arrhythmias was similar to these critical thermal maxima. The considerable thermal plasticity of f Hmax demonstrated in the present study is entirely consistent with eurythermal ecology of killifish, as shown previously for another eurythermal fish Gillichthys mirabilis .

Membrane and calcium clock mechanisms contribute variably as a function of temperature to setting cardiac pacemaker rate in zebrafish Danio rerio - James L. Marchant; Anthony P. Farrell (Journal of Fish Biology, 2019)
Here, we show that heart rate in zebrafish Danio rerio is dependent upon two pacemaking mechanisms and it possesses a limited ability to reset the cardiac pacemaker with temperature acclimation. Electrocardiogram recordings, taken from individual, anaesthetised zebrafish that had been acclimated to 18, 23 or 28°C were used to follow the response of maximum heart rate ( f Hmax ) to acute warming from 18°C until signs of cardiac failure appeared (up to c . 40°C). Because f Hmax was similar across the acclimation groups at almost all equivalent test temperatures, warm acclimation was limited to one significant effect, the 23°C acclimated zebrafish had a significantly higher (21%) peak f Hmax and reached a higher (3°C) test temperature than the 18°C acclimated zebrafish. Using zatebradine to block the membrane hyperpolarisation‐activated cyclic nucleotide–gated channels (HCN) and examine the contribution of the membrane clock mechanisms to cardiac pacemaking, f Hmax was significantly reduced (by at least 40%) at all acute test temperatures and significantly more so at most test temperatures for zebrafish acclimated to 28°C vs . 23°C. Thus, HCN channels and the membrane clock were not only important, but could be modified by thermal acclimation. Using a combination of ryanodine (to block sarcoplasmic calcium release) and thapsigargin (to block sarcoplasmic calcium reuptake) to examine the contribution of sarcoplasmic reticular handling of calcium and the calcium clock, f Hmax was again consistently reduced independent of the test temperature and acclimation temperature, but to a significantly lesser degree than zatebradine for zebrafish acclimated to both 28 and 18°C. Thus, the calcium clock mechanism plays an additional role in setting pacemaker activity that was independent of temperature. In conclusion, the zebrafish cardiac pacemaker has a limited temperature acclimation ability compared with known effects for other fishes and involves two pacemaking mechanisms, one of which was independent of temperature.

RGD-decorated cholesterol stabilized polyplexes for targeted siRNA delivery to glioblastoma cells - Bo Lou; Kate Connor; Kieron Sweeney; Ian S. Miller; Alice O’Farrell; Eduardo Ruiz-Hernandez; David M. Murray; Garry P. Duffy; Alan Wolfe; Enrico Mastrobattista; Annette T. Byrne; Wim E. Hennink (Drug Delivery and Translational Research, 2019)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

Applying species distribution modelling to improving conservation based decisions: a gap analysis of Trinidad and Tobago’s endemic vascular plants - Joshua A. Spiers; Michael P. Oatham; Luke V. Rostant; Aidan D. Farrell (Biodiversity and Conservation, 2018)

Long‐Term Consequences of European Invasions - Julianne Farrell; Myron P. Zalucki (Conservation Biology, 2018)

Editorial July 2018 - A. P. Farrell (Journal of Fish Biology, 2018)

A three‐phase excess post‐exercise oxygen consumption in Atlantic salmon Salmo salar and its response to exercise training - Y. Zhang; G. Claireaux; H. Takle; S. M. Jørgensen; A. P. Farrell (Journal of Fish Biology, 2018)
The recovery of oxygen uptake to the standard metabolic rate (SMR) following exhaustive chasing exercise in Atlantic salmon Salmo salar parr occurred in three phases (rapid, plateau and slow). The initial recovery phase lasted 0·7 h and contributed 16% to the total excess post‐exercise oxygen consumption (EPOC). It was followed by a longer plateau phase that contributed 53% to the total EPOC. The slow recovery phase that completed recovery of SMR, which has not been reported previously, made a 31% contribution to the total EPOC. The plasticity of EPOC was demonstrated in exercise‐trained fish. Exercise training increased EPOC by 39% when compared with control fish (mean ± S.E., 877·7 ± 73·1 v . 629·2 ± 53·4 mg O 2 kg −1 , d.f. = 9, P 0·05), with the duration of the plateau phase increasing by 38% (4·7 ± 0·58 v . 3·4 ± 0·16 h, d.f. = 9, P 0·05) and the contribution of the slow phase to the total EPOC increasing by 80% (173·9 ± 23·9 v . 312·5 ± 50·4 mg O 2 kg −1 , d.f. = 9, P v . 513·6 ± 43·1 mg O 2 kg −1 ; d.f. = 9, P = 0·01). To substantiate the hypothesis that the plateau and slow recovery phase of EPOC was related to general metabolic recovery following exhaustive exercise, the time‐course for recovery of SMR was compared with previously published metabolite recovery profiles. The final phase of metabolic recovery was temporally associated with the final phases of gluconeogenesis, lactate oxidation and muscle intracellular pH regulation. Therefore, the plasticity of the latter phase of EPOC agreed with the known effects of exercise training in fishes.

A lake classification concept for a more accurate global estimate of the dissolved inorganic carbon export from terrestrial ecosystems to inland waters - Fabian Engel; Kaitlin J. Farrell; Ian M. McCullough; Facundo Scordo; Blaize A. Denfeld; Hilary A. Dugan; Elvira de Eyto; Paul C. Hanson; Ryan P. McClure; Peeter Nõges; Tiina Nõges; Elizabeth Ryder; et al. (The Science of Nature, 2018)

Mechanisms of thermal adaptation and evolutionary potential of conspecific populations to changing environments - Zhongqi Chen; Anthony P. Farrell; Amanda Matala; Shawn R. Narum (Molecular Ecology, 2018)
Heterogeneous and ever‐changing thermal environments drive the evolution of populations and species, especially when extreme conditions increase selection pressure for traits influencing fitness. However, projections of biological diversity under scenarios of climate change rarely consider evolutionary adaptive potential of natural species. In this study, we tested for mechanistic evidence of evolutionary thermal adaptation among ecologically divergent redband trout populations ( Oncorhynchus mykiss gairdneri ) in cardiorespiratory function, cellular response and genomic variation. In a common garden environment, fish from an extreme desert climate had significantly higher critical thermal maximum ( p .05) and broader optimum thermal window for aerobic scope (>3°C) than fish from cooler montane climate. In addition, the desert population had the highest maximum heart rate during warming (20% greater than montane populations), indicating improved capacity to deliver oxygen to internal tissues. In response to acute heat stress, distinct sets of cardiac genes were induced among ecotypes, which helps to explain the differences in cardiorespiratory function. Candidate genomic markers and genes underlying these physiological adaptations were also pinpointed, such as genes involved in stress response and metabolic activity ( hsp40 , ldh‐b and camkk2 ). These markers were developed into a multivariate model that not only accurately predicted critical thermal maxima, but also evolutionary limit of thermal adaptation in these specific redband trout populations relative to the expected limit for the species. This study demonstrates mechanisms and limitations of an aquatic species to evolve under changing environments that can be incorporated into advanced models to predict ecological consequences of climate change for natural organisms.

A rainbow trout Oncorhynchus mykiss strain with higher aerobic scope in normoxia also has superior tolerance of hypoxia - Y. Zhang; T. M. Healy; W. Vandersteen; P. M. Schulte; A. P. Farrell (Journal of Fish Biology, 2018)
This study compared parr from three strains of rainbow trout Oncorhynchus mykiss to examine intraspecific variation in metabolic traits, hypoxia tolerance and upper thermal tolerance in this species. At the strain level, variation in absolute aerobic scope (AAS), critical oxygen level (O 2crit ), incipient lethal oxygen saturation (ILOS) and critical thermal maximum (CT max ) generally exhibited consistent differences among the strains, suggesting the possibility of functional associations among these traits. This possibility was further supported at the individual level by a positive correlation between ILOS and O 2crit and a negative correlation between O 2crit and AAS. These results indicate that intraspecific differences in hypoxia tolerance among strains of O. mykiss may be primarily determined by differences in the ability to maintain oxygen uptake in hypoxia and that variation in aerobic scope in normoxia probably plays a role in determining the ability of these fish to sustain metabolism aerobically as water oxygen saturation is reduced.

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

Determinants of coronary blood flow in sandbar sharks, Carcharhinus plumbeus - Georgina K. Cox; Richard W. Brill; Kaitlin A. Bonaro; Anthony P. Farrell (Journal of Comparative Physiology B, 2017)

Relationship between cardiac performance and environment across populations of Atlantic salmon (Salmo salar): a common garden experiment implicates local adaptation - Kayla J. Gradil; Shawn R. Garner; Chris C. Wilson; Anthony P. Farrell; Bryan D. Neff (Evolutionary Ecology, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Seasonal migration of the starry smooth‐hound shark Mustelus asterias as revealed from tag‐recapture data of an angler‐led tagging programme - N. W. P. Brevé; H. V. Winter; H. M. J. Van Overzee; E. D. Farrell; P. A. Walker (Journal of Fish Biology, 2016)
The primary aim of this long‐term angler‐led tagging programme was to gain information about seasonal changes in distribution of the starry smooth‐hound shark Mustelus asterias , along the Dutch coast for management and conservation purposes. Between 2011 and 2014, M. asterias comprised 92·6% ( n = 2418) of the total elasmobranch catch ( n = 2612) by the licenced group of taggers within the Dutch Delta of which 2244 M. asterias were fin‐tagged with plastic rototags. Sex and total length ( L T ) composition inside the eastern tidal basin (Oosterschelde) were significantly different, i.e. more females and larger individuals, than outside indicating a pupping ground, which was confirmed by the capture of 30 newborn pups (≤32 cm). The distribution pattern of reported recaptured M. asterias (return‐rate 3·6%, n = 80) showed a circannual migration between summering in the southern North Sea and wintering in the English Channel and the Bay of Biscay, and suggests that M. asterias is philopatric. The Dutch angling season for M. asterias runs from approximately mid‐May to mid‐October when the water temperature is above 13° C. Recaptures of eight mature females, but no males in the Bay of Biscay, indicate partial spatial segregation by sex, where mature females migrate over larger distances than immature females and males. These observations, with the absence of recaptures in other known summering areas ( i.e. the Irish Sea and Bristol Channel), suggest that the southern North Sea is used by a separate population. Implications for management and recommendations to improve and expand the study approach are discussed.

Quantification of ventricular β 2 ‐adrenoceptor density and ligand binding affinity in wild sockeye salmon Oncorhynchus nerka smolts using a novel modification to the tritiated ligand technique - A. T. Goulding; A. P. Farrell (Journal of Fish Biology, 2016)
A new, image‐based, tritiated ligand technique for measuring cardiac β 2 ‐adrenoceptor (β 2 ‐AR) binding characteristics was developed and validated with adult rainbow trout Oncorhynchus mykiss hearts so that the tissue limitation of traditional receptor binding techniques could be overcome and measurements could be made in hearts nearly 14‐times smaller than previously used. The myocardial cell‐surface (functional) β 2 ‐AR density of O. nerka smolts sampled at the headwaters of the Chilko River was 54·2 fmol mg protein −1 and about half of that previously found in return migrating adults of the same population, but still more than twice that of adult hatchery O. mykiss (21·1 fmol mg protein −1 ). This technique now opens the possibility of investigating cardiac receptor density in a much wider range of fish species and life stages.

Laboratory rearing of wild Arctic cod Boreogadus saida from egg to adulthood - D. Kent; H. E. Drost; J. Fisher; T. Oyama; A. P. Farrell (Journal of Fish Biology, 2016)
The techniques and protocols used to successfully capture, transport and breed Arctic cod Boreogadus saida , as well as to rear their larvae through to adulthood are summarized. Breeding B. saida will increase the opportunity to study this fish species, which is a critical part of the Arctic food web.

Upper thermal limits of the hearts of Arctic cod Boreogadus saida : adults compared with larvae - H. E. Drost; J. Fisher; F. Randall; D. Kent; E. C. Carmack; A. P. Farrell (Journal of Fish Biology, 2016)
Wild adult and reared larval Boreogadus saida were acclimated to 3·5° C before testing their cardiac response to acute warming. Heart rate transition temperatures during warming were similar for adult and larval hearts, except that the maximum temperature for heart rate was 3° C warmer for adults. Thus, in a rapidly warming Arctic Ocean, the upper temperature limit for larval rather than adult B. saida appears more likely to dictate the southern range of the species.

The measurement of specific dynamic action in fishes - D. Chabot; R. Koenker; A. P. Farrell (Journal of Fish Biology, 2016)
Specific dynamic action ( SDA ) is the postprandial increase in oxygen uptake. Whereas it is easy to measure in fishes that remain calm and motionless during the entire digestion period, spontaneous locomotor activity is a frequent problem that leads to overestimation of SDA amplitude and magnitude (area under the curve, bound by the standard metabolic rate, SMR ). Few studies have attempted to remove the effect of fish activity on SDA . A new method, non‐parametric quantile regression, is described to estimate SDA even when pronounced circadian activity cycles are present. Data from juvenile Atlantic cod Gadus morhua are used to demonstrate its use and advantages compared with traditional techniques. Software (scripts in the R language) is provided to facilitate its use.

The determination of standard metabolic rate in fishes - D. Chabot; J. F. Steffensen; A. P. Farrell (Journal of Fish Biology, 2016)
This review and data analysis outline how fish biologists should most reliably estimate the minimal amount of oxygen needed by a fish to support its aerobic metabolic rate (termed standard metabolic rate; SMR ). By reviewing key literature, it explains the theory, terminology and challenges underlying SMR measurements in fishes, which are almost always made using respirometry (which measures oxygen uptake, Ṁ O 2 ). Then, the practical difficulties of measuring SMR when activity of the fish is not quantitatively evaluated are comprehensively explored using 85 examples of Ṁ O 2 data from different fishes and one crustacean, an analysis that goes well beyond any previous attempt. The main objective was to compare eight methods to estimate SMR . The methods were: average of the lowest 10 values (low10) and average of the 10% lowest Ṁ O 2 values, after removing the five lowest ones as outliers (low10%), mean of the lowest normal distribution ( MLND ) and quantiles that assign from 10 to 30% of the data below SMR ( q 0·1 , q 0·15 , q 0·2 , q 0·25 and q 0·3 ). The eight methods yielded significantly different SMR estimates, as expected. While the differences were small when the variability was low amongst the Ṁ O 2 values, they were important (>20%) for several cases. The degree of agreement between the methods was related to the c.v . of the observations that were classified into the lowest normal distribution, the c.v. MLND ( C.V. MLND ). When this indicator was low (≤5·4), it was advantageous to use the MLND , otherwise, one of the q 0·2 or q 0·25 should be used. The second objective was to assess if the data recorded during the initial recovery period in the respirometer should be included or excluded, and the recommendation is to exclude them. The final objective was to determine the minimal duration of experiments aiming to estimate SMR . The results show that 12 h is insufficient but 24 h is adequate. A list of basic recommendations for practitioners who use respirometry to measure SMR in fishes is provided.

Pragmatic perspective on aerobic scope: peaking, plummeting, pejus and apportioning - A. P. Farrell (Journal of Fish Biology, 2016)
A major challenge for fish biologists in the 21st century is to predict the biotic effects of global climate change. With marked changes in biogeographic distribution already in evidence for a variety of aquatic animals, mechanistic explanations for these shifts are being sought, ones that then can be used as a foundation for predictive models of future climatic scenarios. One mechanistic explanation for the thermal performance of fishes that has gained some traction is the oxygen and capacity‐limited thermal tolerance ( OCLTT ) hypothesis, which suggests that an aquatic organism's capacity to supply oxygen to tissues becomes limited when body temperature reaches extremes. Central to this hypothesis is an optimum temperature for absolute aerobic scope ( AAS , loosely defined as the capacity to deliver oxygen to tissues beyond a basic need). On either side of this peak for AAS are pejus temperatures that define when AAS falls off and thereby reduces an animal's absolute capacity for activity. This article provides a brief perspective on the potential uses and limitations of some of the key physiological indicators related to aerobic scope in fishes. The intent is that practitioners who attempt predictive ecological applications can better recognize limitations and make better use of the OCLTT hypothesis and its underlying physiology.

Oxygen uptake in Pacific salmon Oncorhynchus spp.: when ecology and physiology meet - E. J. Eliason; A. P. Farrell (Journal of Fish Biology, 2016)
Over the past several decades, a substantial amount of research has examined how cardiorespiratory physiology supports the diverse activities performed throughout the life cycle of Pacific salmon, genus Oncorhynchus . Pioneering experiments emphasized the importance of aerobic scope in setting the functional thermal tolerance for activity in fishes. Variation in routine metabolism can have important performance and fitness consequences as it is related to dominance, aggression, boldness, territoriality, growth rate, postprandial oxygen consumption, life history, season, time of day, availability of shelter and social interactions. Wild fishes must perform many activities simultaneously ( e.g . swim, obtain prey, avoid predators, compete, digest and reproduce) and oxygen delivery is allocated among competing organ systems according to the capacity of the heart to deliver blood. For example, salmonids that are simultaneously swimming and digesting trade‐off maximum swimming performance in order to support the oxygen demands of digestion. As adult Pacific salmonids cease feeding in the ocean prior to their home migration, endogenous energy reserves and cardiac capacity are primarily partitioned among the demands for swimming upriver, sexual maturation and spawning behaviours. Furthermore, the upriver spawning migration is under strong selection pressure, given that Pacific salmonids are semelparous (single opportunity to spawn). Consequently, these fishes optimize energy expenditures in a number of ways: strong homing, precise migration timing, choosing forward‐assist current paths and exploiting the boundary layer to avoid the strong currents in the middle of the river, using energetically efficient swimming speeds, and recovering rapidly from anaerobic swimming. Upon arrival at the spawning ground, remaining energy can be strategically allocated to the various spawning behaviours. Strong fidelity to natal streams has resulted in reproductively isolated populations that appear to be locally adapted physiologically to their specific environmental conditions. Populations with more challenging migrations have enhanced cardiorespiratory performance. Pacific salmonids are able to maintain aerobic scope across the broad range of temperatures encountered historically during their migration; however, climate change‐induced river warming has created lethal conditions for many populations, raising conservation concerns. Despite considerable research examining cardiorespiratory physiology in Pacific salmonids over the last 70 years, critical knowledge gaps are identified.

Cardiorespiratory responses to haemolytic anaemia in rainbow trout Oncorhynchus mykiss - D. K. Gold; T. Loirat; A. P. Farrell (Journal of Fish Biology, 2015)
To quantify cardiorespiratory response to experimental anaemia in rainbow trout Oncorhynchus mykiss , a 24 h phenylhydrazine treatment was used to reduce haematocrit to almost one third of its initial value over 4–5 days. In response, relative blood velocity in the ventral aorta (an index of cardiac output) progressively increased to more than double to its normocythaemic value and there was no significant change in routine oxygen uptake. Thus, the primary compensatory response to anaemia was an increase in cardiac output.

Upper thermal tolerance of wild‐type, domesticated and growth hormone‐transgenic coho salmon Oncorhynchus kisutch - Z. Chen; R. H. Devlin; A. P. Farrell (Journal of Fish Biology, 2015)
In coho salmon Oncorhynchus kisutch , no significant differences in critical thermal maximum ( c. 26·9° C, C Tmax ) were observed among size‐matched wild‐type, domesticated, growth hormone ( GH )‐transgenic fish fed to satiation, and GH ‐transgenic fish on a ration‐restricted diet. Instead, GH ‐transgenic fish fed to satiation had significantly higher maximum heart rate and Arrhenius breakpoint temperature (mean ± s.e. = 17·3 ± 0·1° C, T AB ). These results provide insight into effects of modified growth rate on temperature tolerance in salmonids, and can be used to assess the potential ecological consequences of GH ‐transgenic fishes should they enter natural environments with temperatures near their thermal tolerance limits.

Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon - S. Matthew Drenner; Scott G. Hinch; Eduardo G. Martins; Nathan B. Furey; Timothy D. Clark; Steven J. Cooke; David A. Patterson; David Robichaud; David W. Welch; Anthony P. Farrell; Richard E. Thomson (Fisheries Oceanography, 2015)
The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon ( Oncorhynchus nerka ) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.

Genetic Differentiation in Response to Selection for Water-Soluble Carbohydrate Content in Perennial Ryegrass (Lolium perenne L.) - J. A. Gallagher; L. B. Turner; A. J. Cairns; M. Farrell; J. A. Lovatt; K. Skøt; I. P. Armstead; M. O. Humphreys; I. Roldan-Ruiz (BioEnergy Research, 2015)

Association between swimming performance, cardiorespiratory morphometry, and thermal tolerance in Atlantic salmon (Salmo salar L.) - Katja Anttila; Sven Martin Jørgensen; Matthew T. Casselman; Gerrit Timmerhaus; Anthony P. Farrell; Harald Takle (Frontiers in Marine Science, 2014)

Oxygen removal from water versus arterial oxygen delivery: calibrating the Fick equation in Pacific salmon - Anthony P. Farrell; Erika J. Eliason; Timothy D. Clark; Maria F. Steinhausen (Journal of Comparative Physiology B, 2014)

Upper thermal limits of cardiac function for Arctic cod Boreogadus saida , a key food web fish species in the Arctic Ocean - H. E. Drost; E. C. Carmack; A. P. Farrell (Journal of Fish Biology, 2014)
The objective of this study was to determine the upper thermal limits of Arctic cod Boreogadus saida by measuring the response of maximum heart rate ( f Hmax ) to acute warming. One set of fish were tested in a field laboratory in Cambridge Bay ( CB ), Nunavut (north of the Arctic Circle), and a second set were tested after air transport to and 6 month temperature acclimation at the Vancouver Aquarium ( VA ) laboratory. In both sets of tests, with B. saida acclimated to 0° C, f Hmax increased during acute warming up to temperatures considerably higher than the acclimation temperature and the near‐freezing Arctic temperatures in which they are routinely found. Indeed, f Hmax increased steadily between 0·5 and 5·5° C, with no significant difference between the CB and VA tests ( P > 0·05) and with an overall mean ± s.e. Q 10 of 2·4 ± 0·5. The first Arrhenius breakpoint temperature ( T AB ) for f Hmax was also statistically indistinguishable for the two sets of tests (mean ± s.e. 3·2 ± 0·3 and 3·6 ± 0·3° C), suggesting that the temperature optimum for B. saida could be reliably measured after live transport to a more southerly laboratory location. Continued warming above 5·5° C revealed a large variability among individuals in the upper thermal limits that triggered cardiac arrhythmia ( T arr ), ranging from 10·2 to 15·2° C with mean ± s.e. 12·4 ± 0·4° C ( n = 11) for the field study. A difference did exist between the CB and VA breakpoint temperatures when the Q 10 value decreased below 2 (the Q 10 breakpoint temperature; T QB ) at 8·0 and 5·5° C, respectively. These results suggest that factors, other than thermal tolerance and associated cardiac performance, may influence the realized distribution of B. saida within the Arctic Circle.

Facing warm temperatures during migration: cardiac mRNA responses of two adult Oncorhynchus nerka populations to warming and swimming challenges - K. Anttila; E. J. Eliason; K. H. Kaukinen; K. M. Miller; A. P. Farrell (Journal of Fish Biology, 2014)
The main findings of the current study were that exposing adult sockeye salmon Onchorhynchus nerka to a warm temperature that they regularly encounter during their river migration induced a heat shock response at an mRNA level, and this response was exacerbated with forced swimming. Similar to the heat shock response, increased immune defence‐related responses were also observed after warm temperature treatment and with a swimming challenge in two different populations (Chilko and Nechako), but with some important differences. Microarray analyses revealed that 347 genes were differentially expressed between the cold (12–13° C) and warm (18–19° C) treated fish, with stress response ( GO :0006950) and response to fungus ( GO :0009620) elevated with warm treatment, while expression for genes involved in oxidative phosphorylation ( GO :0006119) and electron transport chain ( GO :0022900) elevated for cold‐treated fish. Analysis of single genes with real‐time quantitative PCR revealed that temperature had the most significant effect on mRNA expression levels, with swimming and population having secondary influences. Warm temperature treatment for the Chilko population induced expression of heat shock protein ( hsp ) 90α , hsp90β and hsp30 as well as interferon‐inducible protein . The Nechako population, which is known to have a narrower thermal tolerance window than the Chilko population, showed even more pronounced stress responses to the warm treatment and there was significant interaction between population and temperature treatment for hsp90β expression. Moreover, significant interactions were noted between temperature treatment and swimming challenge for hsp90α and hsp30 , and while swimming challenge alone increased expression of these hsp s, the expression levels were significantly elevated in warm‐treated fish swum to exhaustion. In conclusion, it seems that adult O. nerka currently encounter conditions that induce several cellular defence mechanisms during their once‐in‐the‐lifetime migration. As river temperatures continue to increase, it remains to be seen whether or not these cellular defences provide sufficient protection for all O. nerka populations.

Upper thermal tolerance of closely related Danio species - R. Sidhu; K. Anttila; A. P. Farrell (Journal of Fish Biology, 2014)
The main finding of this study was that measuring maximum heart rate during incremental warming was an effective tool to estimate upper thermal limits in three small cyprinid Danio species, which differed significantly. Arrhenius breakpoint temperature for maximum heart rate, purportedly an index of optimum temperature, was 21·2 ± 0·4, 20·1 ± 0·4 and 18·9 ± 0·8° C (mean ± s.e .) for zebrafish Danio rerio , pearl danio Danio albolineatus and glowlight danio Danio choprae , respectively. The temperature where cardiac arrhythmias were first induced during warming ( T arr ) was 36·6 ± 0·7, 36·9 ± 0·8 and 33·2 ± 0·8° C (mean ± s.e .) and critical thermal maximum ( T Cm ) was 39·9 ± 0·1, 38·9 ± 0·1 and 37·2 ± 0·1° C (mean ± s.e .) for D. rerio , D. albolineatus and D. choprae , respectively. The finding that T arr was consistently 3–4° C lower than T Cm suggests that collapse of the cardiac life support system may be a critical trigger for upper temperature tolerance. The upper thermal limits established here, which correlate well with a broad natural environmental temperature range for D. rerio and a narrow one for D. choprae , suggest that upper thermal tolerance may be a genetic trait even among closely related species acclimated to common temperatures.

Preventing overexploitation in a mutualism: partner regulation in the crayfish–branchiobdellid symbiosis - Kaitlin J. Farrell; Robert P. Creed; Bryan L. Brown (Oecologia, 2014)

Investigation of Critical Core Formulation and Process Parameters for Osmotic Pump Oral Drug Delivery - Shahrzad Missaghi; Piyush Patel; Thomas P. Farrell; Hiep Huatan; Ali R. Rajabi-Siahboomi (AAPS PharmSciTech, 2014)

Oral Cancer Chemotherapy Adherence and Adherence Assessment Tools: a Report from North Central Cancer Group Trial N0747 and a Systematic Review of the Literature - Krishna Patel; Nathan R. Foster; Ann Farrell; Nguyet Anh Le-Lindqwister; Josy Mathew; Brian Costello; John Reynolds; Jeffrey P. Meyers; Aminah Jatoi (Journal of Cancer Education, 2013)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Effects of fatty acid provision during severe hypoxia on routine and maximal performance of the in situ tilapia heart - Ben Speers-Roesch; Sabine L. Lague; Anthony P. Farrell; Jeffrey G. Richards (Journal of Comparative Physiology B, 2013)

Process Optimization of a Novel Immediate Release Film Coating System using QbD Principles - Jason Teckoe; Tracey Mascaro; Thomas P. Farrell; Ali R. Rajabi-Siahboomi (AAPS PharmSciTech, 2013)

Low cardiac and aerobic scope in a coastal population of sockeye salmon Oncorhynchus nerka with a short upriver migration - E. J. Eliason; S. M. Wilson; A. P. Farrell; S. J. Cooke; S. G. Hinch (Journal of Fish Biology, 2013)
This study showed that a coastal population (Harrison) of Fraser River sockeye salmon Oncorhynchus nerka had a lower aerobic and cardiac scope compared with interior populations with more challenging upriver spawning migrations, providing additional support to the idea that Fraser River O. nerka populations have adapted physiologically to their local migratory environment.

Climate change simulated by full and mixed-layer ocean versions of CSIRO Mk3.5 and Mk3.0: Large-scale sensitivity - Ian G. Watterson; Siobhan P. O’Farrell (Asia-Pacific Journal of Atmospheric Sciences, 2013)

ECOLOGICAL AND ENVIRONMENTAL PHYSIOLOGY OF FISHES ‐ Edited by F. B. Eddy and R. D. Handy - A. (Tony) P. Farrell (Journal of Fish Biology, 2013)

Commitment to the environment and student support for “green” campus initiatives - Anthony E. Coy; Allison K. Farrell; Katharine P. Gilson; Jody L. Davis; Benjamin Le (Journal of Environmental Studies and Sciences, 2013)

Effects of exogenous abscisic acid and gibberellic acid on pre-maturity α-amylase formation in wheat grains - K. R. Kondhare; P. S. Kettlewell; A. D. Farrell; P. Hedden; J. M. Monaghan (Euphytica, 2012)

The fine line between mutualism and parasitism: complex effects in a cleaning symbiosis demonstrated by multiple field experiments - Bryan L. Brown; Robert P. Creed; James Skelton; Mark A. Rollins; Kaitlin J. Farrell (Oecologia, 2012)

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)

Balancing selection on MHC class I in wild brown trout Salmo trutta - B. O’Farrell; C. Dennis; J. A. Benzie; P. McGinnity; J. Carlsson; E. de Eyto; J. P. Coughlan; F. Igoe; R. Meehan; T. F. Cross (Journal of Fish Biology, 2012)
Evidence is reported for balancing selection acting on variation at major histocompatibility complex (MHC) in wild populations of brown trout Salmo trutta . First, variation at an MHC class I ( satr‐uba )–linked microsatellite locus ( mhc1 ) is retained in small S . trutta populations isolated above waterfalls although variation is lost at neutral microsatellite markers. Second, populations across several catchments are less differentiated at mhc1 than at neutral markers, as predicted by theory. The population structure of these fish was also elucidated.

Water balance trumps ion balance for early marine survival of juvenile pink salmon (Oncorhynchus gorbuscha) - M. Sackville; J. M. Wilson; A. P. Farrell; C. J. Brauner (Journal of Comparative Physiology B, 2012)

The in vitro blood‐O 2 affinity of triploid rainbow trout Oncorhynchus mykiss at different temperatures and CO 2 tensions - C. Verhille; A. P. Farrell (Journal of Fish Biology, 2012)
Blood‐O 2 affinity, Hill number and predicted arterial‐O 2 saturation did not differ between diploid (2N) and triploid (3N) rainbow trout Oncorhynchus mykiss blood when compared under various temperature and CO 2 partial pressure combinations. These results suggest that reduced hypoxia and warm‐water tolerance and aerobic capacity of 3N fishes are not due to altered blood‐O 2 affinity. Further investigation into O 2 transport–diffusion capacity and intracellular pH within 3N fishes may further unravel the mechanisms behind reduced 3N tolerance of suboptimal environments.

Dead fish swimming: a review of research on the early migration and high premature mortality in adult Fraser River sockeye salmon Oncorhynchus nerka - S. G. Hinch; S. J. Cooke; A. P. Farrell; K. M. Miller; M. Lapointe; D. A. Patterson (Journal of Fish Biology, 2012)
Adult sockeye salmon Oncorhynchus nerka destined for the Fraser River, British Columbia are some of the most economically important populations but changes in the timing of their homeward migration have led to management challenges and conservation concerns. After a directed migration from the open ocean to the coast, this group historically would mill just off shore for 3–6 weeks prior to migrating up the Fraser River. This milling behaviour changed abruptly in 1995 and thereafter, decreasing to only a few days in some years (termed early migration), with dramatic consequences that have necessitated risk‐averse management strategies. Early migrating fish consistently suffer extremely high mortality (exceeding 90% in some years) during freshwater migration and on spawning grounds prior to spawning. This synthesis examines multidisciplinary, collaborative research aimed at understanding what triggers early migration, why it results in high mortality, and how fisheries managers can utilize these scientific results. Tissue analyses from thousands of O. nerka captured along their migration trajectory from ocean to spawning grounds, including hundreds that were tracked with biotelemetry, have revealed that early migrants are more reproductively advanced and ill‐prepared for osmoregulatory transition upon their entry into fresh water. Gene array profiles indicate that many early migrants are also immunocompromised and stressed, carrying a genomic profile consistent with a viral infection. The causes of these physiological changes are still under investigation. Early migration brings O. nerka into the river when it is 3–6° C warmer than historical norms, which for some late‐run populations approaches or exceeds their critical maxima leading to the collapse of metabolic and cardiac scope, and mortality. As peak spawning dates have not changed, the surviving early migrants tend to mill in warm lakes near to spawning areas. These results in the accumulation of many more thermal units and longer exposures to freshwater diseases and parasites compared to fish that delay freshwater entry by milling in the cool ocean environment. Experiments have confirmed that thermally driven processes are a primary cause of mortality for early‐entry migrants. The Fraser River late‐run O. nerka early migration phenomenon illustrates the complex links that exist between salmonid physiology, behaviour and environment and the pivotal role that water temperature can have on population‐specific migration survival.

The effect of adrenaline on the temperature dependency of cardiac action potentials in pink salmon Oncorhynchus gorbuscha - S. Ballesta; L. M. Hanson; A. P. Farrell (Journal of Fish Biology, 2012)
Using sharp electrode impalement, action potentials recorded from atrial and ventricular tissue of pink salmon Oncorhynchus gorbuscha generally decreased in duration with increasing test temperature (6, 10, 16 and 20° C). Stimulation of the tissue using 500 nM adrenaline had no significant effect on the duration of the atrial action potential at any test temperature but lengthened the ventricular action potential by ∼17%.

Antitumor bifunctional dinuclear PtII complex BBR3535 forms interduplex DNA cross-links under molecular crowding conditions - Tereza Muchova; Susana M. Quintal; Nicholas P. Farrell; Viktor Brabec; Jana Kasparkova (JBIC Journal of Biological Inorganic Chemistry, 2012)

Thermodynamic stability and energetics of DNA duplexes containing major intrastrand cross-links of second-generation antitumor dinuclear PtII complexes - Jakub Florian; Jana Kasparkova; Nicholas P. Farrell; Viktor Brabec (JBIC Journal of Biological Inorganic Chemistry, 2012)

Using maximum heart rate as a rapid screening tool to determine optimum temperature for aerobic scope in Pacific salmon Oncorhynchus spp. - M. T. Casselman; K. Anttila; A. P. Farrell (Journal of Fish Biology, 2012)
The mean ± s.e. optimum temperature ( T opt ) for aerobic scope in juvenile coho salmon Oncorhynchus kisutch was determined to be 17·0 ± 0·7° C. The repeated measures protocol took 3 weeks to complete the T opt determination using 12 fish tested at five temperatures separated by 2° C increments. This experiment also demonstrated that the T opt was associated with maximum heart rate ( f H ) failing to maintain a Q 10 ‐related increase with temperature. When maximum f H was produced in anaesthetized fish with pharmacological stimulation and f H measured from electrocardiogram recordings during acute warming, the Arrhenius break temperature (ABT) for Q 10 discontinuities in maximum f H (mean ± s.e . = 17·1 ± 0·5° C for 15 ppm clove oil and 16·5 ± 0·2° C for 50 ppm MS‐222) was statistically indistinguishable from the T opt measured using aerobic scope. Such a determination took only 3 days rather than 3 weeks. Therefore, it is proposed that determining ABT for discontinuities in maximum f H in anaesthetized fish presents itself as a valuable, high‐throughput screening tool to assess T opt in fishes, a metric that has become recognized as being extremely valuable in fish biology and fisheries management.

Platinum anticancer agents and antidepressants: desipramine enhances platinum-based cytotoxicity in human colon cancer cells - Peyman Kabolizadeh; Brigitte J. Engelmann; Nicholas Pullen; Jennifer K. Stewart; John J. Ryan; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2012)

A radical approach to beating hypoxia: depressed free radical release from heart fibres of the hypoxia-tolerant epaulette shark (Hemiscyllum ocellatum) - Anthony J. R. Hickey; Gillian M. C. Renshaw; Ben Speers-Roesch; Jeffrey G. Richards; Yuxiang Wang; Anthony P. Farrell; Colin J. Brauner (Journal of Comparative Physiology B, 2012)

Physiological and molecular endocrine changes in maturing wild sockeye salmon, Oncorhynchus nerka, during ocean and river migration - A.-M. Flores; J. M. Shrimpton; D. A. Patterson; J. A. Hills; S. J. Cooke; T. Yada; S. Moriyama; S. G. Hinch; A. P. Farrell (Journal of Comparative Physiology B, 2012)

The efficacy of field techniques for obtaining and storing blood samples from fishes - T. D. Clark; M. R. Donaldson; S. M. Drenner; S. G. Hinch; D. A. Patterson; J. Hills; V. Ives; J. J. Carter; S. J. Cooke; A. P. Farrell (Journal of Fish Biology, 2011)
Prompted by the dramatic increase in the use of blood analyses in fisheries research and monitoring, this study investigated the efficacy of common field techniques for sampling and storing blood from fishes. Three questions were addressed: (1) Do blood samples taken via rapid caudal puncture (the ‘grab‐and‐stab’ technique) yield similar results for live v. sacrificed groups of fishes? (2) Do rapidly obtained caudal blood samples accurately represent blood properties of fishes prior to capture? (3) Does storage of whole blood in an ice slurry for a working day (8·5 h) modify the properties of the plasma? It was shown that haematocrit, plasma ions, metabolites, stress hormones and sex hormones of caudal blood samples were statistically similar when taken from live v. recently sacrificed groups of adult coho salmon Oncorhynchus kisutch . Moreover, this study confirmed by using paired blood samples from cannulated O. kisutch that blood acquired through the caudal puncture technique (mean ± s.e . 142 ± 26 s after capture) was representative of fish prior to capture. Long‐term (8·5 h) cold storage of sockeye salmon Oncorhynchus nerka whole blood caused significant decreases in plasma potassium and chloride, and a significant increase in plasma glucose. Previous research has suggested that these changes largely result from net movements of ions and molecules between the plasma and erythrocytes, movements that can occur within minutes of storage. Thus, blood samples from fishes should be centrifuged as quickly as practicable in the field for separation of plasma and erythrocytes to prevent potentially misleading data.

Anoxic survival of the Pacific hagfish (Eptatretus stoutii) - Georgina K. Cox; Eric Sandblom; Jeffrey G. Richards; Anthony P. Farrell (Journal of Comparative Physiology B, 2011)

Early life stage salinity tolerance of wild and hatchery‐reared juvenile pink salmon Oncorhynchus gorbuscha - A. M. Grant; M. Gardner; L. M. Hanson; A. P. Farrell; C. J. Brauner (Journal of Fish Biology, 2010)
Salinity tolerance in wild (Glendale) and hatchery (Quinsam) pink salmon Oncorhynchus gorbuscha (average mass 0·2 g) was assessed by measuring whole body [Na + ] and [Cl − ] after 24 or 72 h exposures to fresh water (FW) and 33, 66 or 100% sea water (SW). Gill Na + , K + ‐ATPase activity was measured following exposure to FW and 100% SW and increased significantly in both populations after a 24 h exposure to 100% SW. Whole body [Na + ] and whole body [Cl − ] increased significantly in both populations after 24 h in 33, 66 and 100% SW, where whole body [Cl − ] differed significantly between Quinsam and Glendale populations. Extending the seawater exposure to 72 h resulted in no further increases in whole body [Na + ] and whole body [Cl − ] at any salinity, but there was more variability among the responses of the two populations. Per cent whole body water ( c. 81%) was maintained in all groups of fish regardless of salinity exposure or population, indicating that the increase in whole body ion levels may have been related to maintaining water balance as no mortality was observed in this study. Thus, both wild and hatchery juvenile O. gorbuscha tolerated abrupt salinity changes, which triggered an increase in gill Na + , K + ‐ATPase within 24 h. These results are discussed in terms of the preparedness of emerging O. gorbuscha for the marine phase of their life cycle.

Challenges and Opportunities in Establishing Scientific and Regulatory Standards for Assuring Therapeutic Equivalence of Modified Release Products: Workshop Summary Report - Mei-Ling Chen; Vinod P. Shah; Derek Ganes; Kamal K. Midha; James Caro; Prabu Nambiar; Mario L. Rocci; Avinash G. Thombre; Bertil Abrahamsson; Dale Conner; Barbara Davit; Paul Fackler; et al. (The AAPS Journal, 2010)

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

Improved simulation of Australian climate and ENSO‐related rainfall variability in a global climate model with an interactive aerosol treatment - Leon D. Rotstayn; Mark A. Collier; Martin R. Dix; Yan Feng; Hal B. Gordon; Siobhan P. O'Farrell; Ian N. Smith; Jozef Syktus (International Journal of Climatology, 2010)
We assess the simulation of Australian mean climate and rainfall variability in a new version of the CSIRO coupled ocean–atmosphere global climate model (GCM). The new version, called Mark 3.6 (Mk3.6), differs from its recent predecessors (Mk3.0 and Mk3.5) by inclusion of an interactive aerosol scheme, which treats sulfate, dust, sea salt and carbonaceous aerosol. Other changes include an updated radiation scheme and a modified boundary‐layer treatment. Comparison of the mean summer and winter climate simulations in Mk3.6 with those in Mk3.0 and Mk3.5 shows several improvements in the new version, especially regarding winter rainfall and sea‐level pressure. The improved simulation of Australian mean seasonal climate is confirmed by calculation of a non‐dimensional skill score (the ‘ M ‐statistic’), using data from all four seasons. However, the most dramatic improvement occurs in the model's simulation of the leading modes of annual rainfall variability, which we assess using empirical orthogonal teleconnections (EOTs). Compared to its predecessors and several international GCMs, Mk3.6 is best able to capture the spatial pattern of the leading rainfall mode, which represents variability due to the El Niño Southern Oscillation (ENSO). Mk3.6 is also best able to capture the spatial pattern of the second rainfall mode, which corresponds to increased rainfall in the northwest, and decreased rainfall over eastern Australia. We propose a possible mechanism for the improved simulation of rainfall variability in terms of the role of interactive dust in Mk3.6. By further suppressing convection over eastern Australia during El Niño events, dust feedbacks may enhance rainfall variability there, in tune with the model's ENSO cycle. This suggests that an interactive aerosol treatment may be important in a GCM used for the study of Australian climate change and variability. Mechanistic sensitivity studies are needed to further evaluate this hypothesis. Copyright © 2009 Royal Meteorological Society

Zooplankton response to shading effects of free-floating plants in shallow warm temperate lakes: a field mesocosm experiment - M. S. Fontanarrosa; G. Chaparro; P. de Tezanos Pinto; P. Rodriguez; I. O’Farrell (Hydrobiologia, 2010)

Simultaneous biologging of heart rate and acceleration, and their relationships with energy expenditure in free-swimming sockeye salmon (Oncorhynchus nerka) - Timothy Darren Clark; E. Sandblom; S. G. Hinch; D. A. Patterson; P. B. Frappell; A. P. Farrell (Journal of Comparative Physiology B, 2010)

Tensile Strain as a Regulator of Mesenchymal Stem Cell Osteogenesis - E. M. Kearney; E. Farrell; P. J. Prendergast; V. A. Campbell (Annals of Biomedical Engineering, 2010)

Reduced and reversed temperature dependence of blood oxygenation in an ectothermic scombrid fish: implications for the evolution of regional heterothermy? - Timothy Darren Clark; J. L. Rummer; C. A. Sepulveda; A. P. Farrell; C. J. Brauner (Journal of Comparative Physiology B, 2010)

Testing the synergistic effects of GnRH and testosterone on the reproductive physiology of pre‐adult pink salmon Oncorhynchus gorbuscha - G. T. Crossin; S. G. Hinch; S. J. Cooke; D. A. Patterson; A. G. Lotto; G. Van Der Kraak; Y. Zohar; U. Klenke; A. P. Farrell (Journal of Fish Biology, 2010)
To test the hypothesis that the hypothalmic gonadotropin‐releasing hormone (GnRH) and testosterone (T) co‐treatment stimulates both the hypothalmo–pituitary–gonadal (HPG) and hypothalmo–pituitary–interrenal axes, the reproductive and osmoregulatory responses of pre‐adult pink salmon Oncorhynchus gorbuscha were compared after GnRH and T administration either alone or in combination. Relative to controls, neither GnRH nor T treatment resulted in significantly greater ovarian or testicular growth, but co‐treatment significantly increased ovarian growth after 5 months. Interestingly, the stimulation was undetectable after 3 months. However, once daily photoperiod began shortening after the summer solstice, c. 2 months before the natural spawning date, GnRH+T‐treated females were stimulated to produce larger ovaries. Final fish body length and the size of individual eggs did not differ among treatment groups. GnRH+T eggs, however, showed signs of advanced vitellogenesis relative to GnRH‐treated and control eggs, whereas T‐treated eggs became atretic. Testis size increased significantly from initial values and most males were spermiating, but this growth and development were independent of hormone treatments. Final plasma ion, metabolite and cortisol concentrations did not differ among treatment groups. It is concluded that GnRH+T co‐treatment was effective in stimulating female but not male maturation. GnRH and T treatment, however, presumably had little effect on the hypothalmo–pituitary–interrenal axis as observed by ionoregulatory status.

Coronary vascular volume remodelling in rainbow trout Oncorhynchus mykiss - D. L. Simonot; A. P. Farrell (Journal of Fish Biology, 2009)
The 34% increase in relative ventricular mass ( M rv ) resulting from chronic anaemia (induced by an intraperitoneal injection of phenylhydrazine hydrochloride) was accompanied by a 117% increase in coronary vascular volume of diploid rainbow trout Oncorhynchus mykiss . Coronary vascular volume of normocythemic triploid fish was similar to that of normocythemic diploid fish despite a larger M rv . These observations, in combination with previous studies, suggest that the vascularity of compact myocardium in O. mykiss can vary independently of M rv .

Swimming performance and associated ionic disturbance of juvenile pink salmon Oncorhynchus gorbuscha determined using different acceleration profiles - L. Nendick; A. Grant; M. Gardner; M. Sackville; C. J. Brauner; A. P. Farrell (Journal of Fish Biology, 2009)
Swimming performance was assessed in juvenile pink salmon Oncorhynchus gorbuscha (body mass −2 ) and a repeated ramped‐critical swimming speed test. Regardless of the swim protocol, the final swimming speeds did not differ significantly ( P > 0·05) among swim tests and ranged from 4·54 to 5·20 body lengths s −1 . This result supports the hypothesis that at an early life stage, O. gorbuscha display the same fatigue speeds independent of the swimming test utilized. Whole body and plasma [Na + ] and [Cl − ] measured at the conclusion of these tests were significantly elevated when compared with control values ( P 0·05) and appear to be predominantly associated with dehydration rather than net ion gain. Given this finding for a small salmonid, estimates of swim performance can be accurately measured with acceleration tests lasting

Structural consequences of a 3′ → 3′ DNA interstrand cross-link by a trinuclear platinum complex: unique formation of two such cross-links in a 10-mer duplex - Yun Qu; My-Chau Tran; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2009)

The relationship between grain weight and alpha-amylase in winter wheat: varietal comparison from UK field experiments - A. D. Farrell; P. S. Kettlewell (Euphytica, 2009)

Sex differences in circulatory oxygen transport parameters of sockeye salmon (Oncorhynchus nerka) on the spawning ground - Timothy Darren Clark; S. G. Hinch; B. D. Taylor; P. B. Frappell; A. P. Farrell (Journal of Comparative Physiology B, 2009)

Physiological, energetic and behavioural correlates of successful fishway passage of adult sockeye salmon Oncorhynchus nerka in the Seton River, British Columbia - L. B. Pon; S. G. Hinch; S. J. Cooke; D. A. Patterson; A. P. Farrell (Journal of Fish Biology, 2009)
Electromyogram (EMG) radio telemetry was used in conjunction with physiological biopsy to relate prior physiological condition and subsequent swimming energetics and behaviours to passage success of 13 wild adult sockeye salmon Oncorhynchus nerka at a vertical‐slot fishway on the Seton River, British Columbia. At the time of capture, plasma lactate, glucose and cortisol levels indicated that fish were not exhibiting unusually high levels of physiological stress. Very few differences existed between successful and unsuccessful fish in body size, initial plasma physiology and energy state and mean swim speed and energy use during passage. Generally, fish did not employ burst swimming during successful or failed attempts at passage, indicating that failure was probably not related to metabolic acidosis. Plasma Na + concentration was significantly lower in unsuccessful fish ( P O. nerka . Nevertheless, six of 13 fish failed to reascend the fishway and remained in the tailrace of the dam for more than a day on average before moving downstream and away from the dam. During this time, fish were observed actively seeking a means of passage, suggesting that there may have been other, undetermined causes of passage failure.

Calibration of a hand‐held haemoglobin analyser for use on fish blood - T. D. Clark; E. J. Eliason; E. Sandblom; S. G. Hinch; A. P. Farrell (Journal of Fish Biology, 2008)
The HemoCue haemoglobin analyser consistently overestimated haemoglobin concentration ([Hb]) in the blood of all fish species (sockeye salmon Oncorhynchus nerka , Chinook salmon Oncorhynchus tshawytscha , Pacific bluefin tuna Thunnus orientalis and chub mackerel Scomber japonicus ) by 22–50% (9·9–36·0 g l −1 ) over a [Hb] range of 20–160 g l −1 . The systematic nature of the overestimation, however, allowed the formulation of an accurate calibration equation that can be used to correct values of [Hb] measured by the HemoCue in field studies.

Effect of planting stocktype and cultivation treatment on the establishment of Norway spruce on cutaway peatlands - Florence Renou-Wilson; Michael Keane; E. P. Farrell (New Forests, 2008)

Current and future directions for pike ecology and management: a summary and synthesis - P. Anders Nilsson; Christian Skov; John M. Farrell (Hydrobiologia, 2008)

Comparisons of swimming performance in rainbow trout using constant acceleration and critical swimming speed tests - A. P. Farrell (Journal of Fish Biology, 2008)
Maximum swimming performance of seasonally acclimated rainbow trout Oncorhynchus mykiss was compared among short‐duration constant acceleration tests ( U max ) and with the well established, but longer duration critical swimming speed ( U crit ) test. The present results show that U max was insensitive to a range of acceleration rates that differed by more than three‐fold. Thus, test duration could be reduced from 58 to 18 min without affecting the estimate of U max . The value of U max , however, was up to 57% higher than U crit . Only the slowest acceleration rate tested (an increase of 1 cm s −1 every min) had a significantly lower U max , and this was up to 19% higher than U crit . Even so, the potential saving in the test duration was small (70 v. 90 min) when compared with a ramp‐ U crit test (a standard U crit test but with the water velocity initially ramped to c . 50% of the estimated U crit ). Therefore, swim tests that are appreciably shorter in duration than a ramp‐ U crit test result in U max being appreciably greater than U crit . An additional discovery was that the ramp‐ U crit performance of cold‐acclimated rainbow trout was independent of the recovery period between tests. These results may prove useful in making comparisons among different swim test protocols and in designing swim tests that assess fish health and toxicological impacts.

Air breathing minimizes post‐exercise lactate load in the tropical Pacific tarpon, Megalops cyprinoides Broussonet 1782 but oxygen debt is repaid by aquatic breathing - R. M. G. Wells; J. Baldwin; R. S. Seymour; K. A. Christian; A. P. Farrell (Journal of Fish Biology, 2007)
Swimming in a flume at reduced water pO 2 resulted in muscle and blood lactate levels in Pacific tarpon Megalops cyprinoides that were significantly higher when fish did not have access to air. Blood glucose and haematological variables were unchanged throughout the regimes of exercise at two swimming speeds and hypoxia. Strenuous exercise with bouts of burst swimming, however, resulted in both high blood lactate and glucose, and perturbed haematological status with elevated haemoglobin and reduced mean cell‐haemoglobin concentration. Post‐exercise recovery was achieved through aquatic breathing rather than by air breathing. The air‐breathing organ in Pacific tarpon therefore prolonged aerobic activity, but gill breathing was used to repay oxygen debt.

Early performance of native birch (Betula spp.) planted on cutaway peatlands: influence of species, stock types and seedlings size - Florence Renou; Úna Scallan; Michael Keane; E. P. Farrell (European Journal of Forest Research, 2007)

Behaviour and physiology of sockeye salmon homing through coastal waters to a natal river - Glenn T. Crossin; Scott G. Hinch; Steven J. Cooke; David W. Welch; Sonia D. Batten; David A. Patterson; Glen Van Der Kraak; J. Mark Shrimpton; Anthony P. Farrell (Marine Biology, 2007)

The hypoxic threshold for maximum cardiac performance in rainbow trout Oncorhynchus mykiss (Walbaum) during simulated exercise conditions at 18° C - L. M. Hanson; A. P. Farrell (Journal of Fish Biology, 2007)
Perfused rainbow trout Oncorhynchus mykiss hearts exposed to simulated exercise conditions (hypoxia, hyperkalemia and acidosis) at 18° C experienced complete failure of maximum cardiac performance at oxygen tensions P

A novel technique for estimating the compact myocardium in fishes reveals surprising results for an athletic air‐breathing fish, the Pacific tarpon - A. P. Farrell; D. L. Simonot; R. S. Seymour; T. D. Clark (Journal of Fish Biology, 2007)
A method for quickly assessing the relative proportion of compact myocardium in the ventricle of teleosts is introduced and used in juvenile Pacific tarpon Megalops cyprinoides , a member of the only air‐breathing elopomorph teleost genus. The proportion of compact myocardium increased with body mass, reaching up to 60% of the ventricular mass. The finding for tarpon was a surprising discovery since recent literature has suggested that air breathing evolved primarily as means of supplying oxygen to the fish heart during activity. The present data, which represent the first quantitative assessment of the compact myocardium for any air‐breathing fish, suggest that myocardial oxygen supply in the tarpon is supplemented by the coronary circulation associated with compact myocardium during exercise, while air breathing is important during aquatic hypoxia. Compact myocardium was also measured as a point of reference in an extant representative from a more ancient fish lineage than the elopomorphs, the water‐breathing spiny dogfish Squalus acanthias and found to be only 9% of ventricular mass. In conclusion, the presence of a coronary circulation in extant elasmobranchs may mean that the coronary circulation evolved well before air breathing in fishes and, for tarpon at least, the coronary oxygen supply to the ventricular myocardium has not necessarily been superseded by air breathing.

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

Validation of the hepatic portal vein cannulation technique using Atlantic salmon Salmo salar L. - E. J. Eliason; A. Kiessling; A. Karlsson; B. Djordjevic; A. P. Farrell (Journal of Fish Biology, 2007)
This study assessed the hepatic portal vein cannulation technique and surgical recovery in Atlantic salmon Salmo salar. Haematocrit levels were maintained and blood variables, including cortisol, returned to baseline levels within 1–3 days post‐surgery, indicating that this technique is a viable, useful method to study the digestive physiology of fishes.

Above- and belowground biomass measurements in an unthinned stand of Sitka spruce (Picea sitchensis (Bong) Carr.) - Carly Green; Brian Tobin; Michael O’Shea; Edward P. Farrell; Kenneth A. Byrne (European Journal of Forest Research, 2007)

Acute and Sublethal Toxicities of Rotenone in Juvenile Rainbow Trout (Oncorhynchus mykiss): Swimming Performance and Oxygen Consumption - W. W. Cheng; A. P. Farrell (Archives of Environmental Contamination and Toxicology, 2007)

A high resolution green area index for modelling the seasonal dynamics of CO2 exchange in peatland vascular plant communities - David Wilson; Jukka Alm; Terhi Riutta; Jukka Laine; Kenneth A. Byrne; Edward P. Farrell; Eeva-Stiina Tuittila (Plant Ecology, 2007)

Seasonal and spatial variability of soil respiration in four Sitka spruce stands - Gustavo Saiz; Carly Green; Klaus Butterbach-Bahl; Ralf Kiese; Valerio Avitabile; Edward P. Farrell (Plant and Soil, 2006)

Fatigue is a behavioural response in respirometer‐confined smallmouth bass - S. J. Peake; A. P. Farrell (Journal of Fish Biology, 2006)
Fatigue in respirometer‐confined smallmouth bass Micropterus dolomieu was confirmed as being largely a behavioural response, and not brought about by depletion of anaerobic fuel stores. While data collected from these fish did not preclude the possibility that the behavioural response was triggered when some physiological threshold was exceeded, locomotory gait transition patterns in confined fish exposed to increasing water velocities support an alternate hypothesis. This is that fatigue is a behavioural decision made at (or near) the gait transition swimming speed, in an effort to avoid activity that, by virtue of the limited space in a typical respirometer, is energetically inefficient and biomechanically difficult.

Stand age‐related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH‐BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)
The effect of stand age on soil respiration and its components was studied in a first rotation Sitka spruce chronosequence composed of 10‐, 15‐, 31‐, and 47‐year‐old stands established on wet mineral gley in central Ireland. For each stand age, three forest stands with similar characteristics of soil type and site preparation were used. There were no significant differences in total soil respiration among sites of the same age, except for the case of a 15‐year‐old stand that had lower soil respiration rates due to its higher productivity. Soil respiration initially decreased with stand age, but levelled out in the older stands. The youngest stands had significantly higher respiration rates than more mature sites. Annual soil respiration rates were modelled by means of temperature‐derived functions. The average Q 10 value obtained treating all the stands together was 3.8. Annual soil respiration rates were 991, 686, 556, and 564 g C m −2 for the 10‐, 15‐, 31‐, and 47‐year‐old stands, respectively. We used the trenching approach to separate soil respiration components. Heterotrophic respiration paralleled soil organic carbon dynamics over the chronosequence, decreasing with stand age to slightly increase in the oldest stand as a result of accumulated aboveground litter and root inputs. Root respiration showed a decreasing trend with stand age, which was explained by a decrease in fine root biomass over the chronosequence, but not by nitrogen concentration of fine roots. The decrease in the relative contribution of autotrophic respiration to total soil CO 2 efflux from 59.3% in the youngest stand to 49.7% in the oldest stand was explained by the higher activity of the root system in younger stands. Our results show that stand age should be considered if simple temperature‐based models to predict annual soil respiration in afforestation sites are to be used.

Stand age-related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH-BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)

Road Verge and Rangeland Plant Communities in the Southern Karoo: Exploring What Influences Diversity, Dominance and Cover - P. J. O’FARRELL; S. J. MILTON (Biodiversity and Conservation, 2006)

Acute Didecyl Dimethyl Ammonium Chloride Toxicity to Larval Lake Sturgeon, Acipenser fulvescens Rafinesque, Walleye Sander vitreus Mitchill, and Northern Pike, Esox lucius Linnaeus - M. A. Gray; S. J. Peake; A. P. Farrell; R. Bruch (Bulletin of Environmental Contamination and Toxicology, 2005)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

The relationships between fish health, metabolic rate, swimming performance and recovery in return‐run sockeye salmon, Oncorhynchus nerka (Walbaum) - K B Tierney; A P Farrell (Journal of Fish Diseases, 2004)
The repeat swimming ability and oxygen uptake ( M o 2 ) of adult sockeye salmon, Oncorhynchus nerka (Walbaum), were assessed at ambient water temperatures at three field locations along their migration route. Following these measurements, internal and external fish condition was evaluated according to United States Environmental Protection Agency guidelines. Here we report on the physiological characteristics of fish having either moderate or severe levels of disease and injury. Routine oxygen uptake ( M o 2 ) did not differ between healthy fish and those with indices of ill health. In contrast, fish classified as sick, which included conditions of damaged internal organs, an Ichthyophonus spp. heart infection, a Saprolegnia spp. gill infection, and skin wounds, had a lower post‐exercise M o 2 and were unable to repeat their critical swim speed ( U crit ) on the second swim test. Moderate levels of disease or injury did not significantly affect either U crit or post‐exercise M o 2 . We conclude that the ability of adult salmon to recover quickly from exercise may be a useful indicator of sublethal pathologies.

The differential leucocyte landscape of four teleosts: juvenile Oncorhynchus kisutch , Clupea pallasi , Culaea inconstans and Pimephales promelas - K. B. Tierney; A. P. Farrell; C. J. Kennedy (Journal of Fish Biology, 2004)
The appearance and proportions of morphologically distinct leucocytes (monocytes, thrombocytes, lymphocytes and diverse forms of granulocytes) encountered in the blood of four teleost species: coho salmon Oncorhynchus kisutch , Pacific herring Clupea pallasi , brook stickleback Culaea inconstans and fathead minnow Pimephales promelas , are presented, along with examples of how water quality influenced their relative proportions. The results clearly show that relative leucocyte number responds significantly and differently to changes in water quality. The value of using differential white cell counting as a quick and inexpensive component of assaying immune system alterations is discussed.

Exposure to solar radiation increases damage to both host tissues and algal symbionts of corals during thermal stress - Michael P. Lesser; Julianne H. Farrell (Coral Reefs, 2004)

Energetics and morphology of sockeye salmon: effects of upriver migratory distance and elevation - G. T. Crossin; S. G. Hinch; A. P. Farrell; D. A. Higgs; A. G. Lotto; J. D. Oakes; M. C. Healey (Journal of Fish Biology, 2004)
Depending on population, wild Fraser River sockeye salmon Oncorhynchus nerka travel distances of 1100 km and ascend elevations ranging from near sea‐level to 1200 m to reach spawning areas. Populations embarking on distant, high elevation migrations ( i.e . Early Stuart, Chilko and Horsefly populations) began their upriver spawning migrations with higher densities of somatic energy ( c . 9·2 to 9·8 MJ kg −1 ) and fewer eggs ( c . 3200 to 3800) than populations making shorter, low elevation migrations ( i.e . Weaver and Adams; c . 7·1 to 8·3 MJ kg −1 gross somatic energy and c . 4300 to 4700 eggs). Populations making difficult upriver migrations also had morphologies that were smaller and more fusiform than populations making less difficult migrations, traits that may facilitate somatic energy conservation by reducing transport costs. Indeed, fish travelling long distances expended less somatic energy per unit of migratory difficulty than those travelling shorter distances (2·8 to 3·8 kJ v . 10–1400 kJ). Consistent with evolutionary theory, difficult migrations appear to select for energy efficiency but ultimately fish making more difficult migrations produce fewer eggs, even when differences in body length have been accounted for. Despite large among‐population differences in somatic energy at the start of upriver migration, all populations completed migration and spawning, and subsequently died, with c . 4 MJ kg −1 of energy remaining, a level which may reflect a threshold to sustain life.

Somatic energy of sockeye salmon Oncorhynchus nerka at the onset of upriver migration: a comparison among ocean climate regimes - Glenn T. Crossin; Scott G. Hinch; Anthony P. Farrell; David A. Higgs; Michael C. Healey (Fisheries Oceanography, 2004)
We examined somatic energy patterns in two stocks (Chilko and Early Stuart) of adult Fraser River (British Columbia, Canada) sockeye salmon ( Oncorhynchus nerka ), collected at the end of their ocean residency, spanning years across different climate regimes. Both stocks had high levels of somatic energy in years with high open ocean productivity (1956, 1957, 2001 and 2002), and relatively low levels in years with poor open ocean productivity (1999 and 2000). For Early Stuart sockeye, energy levels in 1999 and 2000 were approximately 15% lower (∼1.5 MJ kg −1 ) than that in the 1950s, an amount of energy equivalent to that necessary for migrating 600 km upriver. In recent years (2001 and 2002), energy levels have increased by about 9% for both stocks. Low energy levels at the onset of upriver migration, particularly in years of energetically demanding in‐river conditions, such as high flows or temperatures, are likely to contribute to prespawning and en route mortality in Fraser sockeye.

The effect of temperature and acclimation period on repeat swimming performance in cutthroat trout - M. J. MacNutt; S. G. Hinch; A. P. Farrell; S. Topp (Journal of Fish Biology, 2004)
Hatchery cutthroat trout Oncorhynchus clarki clarki were used to examine the effects of 48 h and 3 week temperature acclimation periods on critical swimming speed ( U crit ). The U crit was determined for fish at acclimation temperatures of 7, 14 and 18° C using two consecutive ramp‐ U crit tests in mobile Brett‐type swim tunnels. An additional group was tested at the stock's ambient rearing temperature of 10° C. The length of the temperature acclimation period had no significant effect on either the first or the second U crit ( U crit‐1 and U crit‐2 , respectively) or on the recovery ratio (the quotient of U crit‐2 U crit‐1 −1 ). As anticipated, there was a significant positive relationship between U crit‐1 and temperature ( P U crit‐2 and temperature ( P = 0·10). Acclimation temperature had no significant effect ( P = 0·71) on the recovery ratio. These results indicate that a 48 h acclimation to experimental temperatures within the range of −3 to +8° C of the acclimation temperature may be sufficient in studies of swimming performance with this species. This ability to acclimate rapidly is probably adaptive for cutthroat trout and other species that occupy thermally variable environments.

Preconditioning stimuli do not benefit the myocardium of hypoxia-tolerant rainbow trout ( Oncorhynchus mykiss) - Johannes Overgaard; Jonathan A. W. Stecyk; Hans Gesser; Tobias Wang; A. Kurt Gamperl; Anthony P. Farrell (Journal of Comparative Physiology B, 2004)

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Synteny between a major heading-date QTL in perennial ryegrass (Lolium perenne L.) and the Hd3 heading-date locus in rice - I. P. Armstead; L. B. Turner; M. Farrell; L. Skøt; P. Gomez; T. Montoya; I. S. Donnison; I. P. King; M. O. Humphreys (Theoretical and Applied Genetics, 2004)

Oxygen uptake of growth hormone transgenic coho salmon during starvation and feeding - R. A. Leggatt; R. H. Devlin; A. P. Farrell; D. J. Randall (Journal of Fish Biology, 2003)
Oxygen uptake of growth hormone transgenic coho salmon Oncorhynchus kisutch was measured in individual fish with a closed‐system respirometer and was compared with that of similar‐sized non‐transgenic control coho salmon during starvation and when fed a fixed ration or to satiation. Transgenic and control fish did not differ in their standard oxygen uptake after 4 days of starvation, although control fish had a higher routine oxygen uptake, scope for spontaneous activity and initial acclimation oxygen uptake. During feeding, transgenic fish ate significantly more than control fish, and had an overall oxygen uptake that was 1·7 times greater than control fish. When fish that had eaten the same per cent body mass were compared, transgenic fish had an oxygen uptake that was 1·4 times greater than control fish. Differences in oxygen uptake in growth hormone transgenic coho salmon and non‐transgenic fish appear to be due to the effects of feeding, acclimation and activity level, and not to a difference in basal metabolism.

Swimming performance, oxygen consumption and excess post‐exercise oxygen consumption in adult transgenic and ocean‐ranched coho salmon - C. G. Lee; R. H. Devlin; A. P. Farrell (Journal of Fish Biology, 2003)
Routine oxygen consumption ( M o 2 ) was 35% higher in 1 day starved and 21% higher in 4 day starved adult transgenic coho salmon Oncorhynchus kisutch relative to end of migration ocean‐ranched coho salmon. Critical swimming speed ( U crit ) and M o 2 at U crit ( M o 2max ) were significantly lower in 4 day starved transgenic coho salmon (1·25 BL s −1 ; 8·79 mg O 2 kg −1 min −1 ) compared to ocean‐ranched coho salmon (1·60 BL s −1 ; 9·87 mg O 2 kg −1 min −1 ). Transgenic fish swam energetically less efficiently than ocean‐ranched fish, as indicated by a poorer swimming economy at U crit ( M o 2max ). Although M o 2max was lower in transgenic coho salmon, the excess post‐exercise oxygen consumption (EPOC) measured during the first 20 min of recovery was significantly larger in transgenic coho salmon (44·1 mg O 2 kg −1 ) compared with ocean‐ranched coho salmon (34·2 mg O 2 kg −1 ), which had a faster rate of recovery.

Cooperative effects in long-range 1,4 DNA-DNA interstrand cross-links formed by polynuclear platinum complexes: an unexpected syn orientation of adenine bases outside the binding sites - Yun Qu; Neel J. Scarsdale; My-Chau Tran; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2003)

Green‐fluorescent proteins in Caribbean corals - Charles H. Mazel; Michael P. Lesser; Maxim Y. Gorbunov; Thomas M. Barry; Julianne H. Farrell; Kevin D. Wyman; Paul G. Falkowski (Limnology and Oceanography, 2003)
Fluorescent pigments in several Indo‐Pacific and Caribbean anthozoans have recently been identified as proteins related to the Green‐fluorescent protein (GFP) of the hydromedusa Aequorea victoria . Here we show that GFP is widely distributed in many Caribbean species. The fluorescence excitation and emission spectra for the pigment are similar to those reported elsewhere for coral and noncoral GFP and the fluorescence quantum yield is estimated to be 35%. Spectral and molecular characterization of the isolated protein clearly show it to be GFP, and laboratory and in situ fluorescence measurements and Western blot analysis show that it is widespread. Bathymetric studies of GFP content using Western blots for the ecologically important congeneric corals Montastraea faveolata and Montastraea cavernosa show that there is no significant correlation between depth and GFP concentration. Nucleotide sequence data of GFP from M. faveolata and M. cavernosa show 88.2% sequence homology with each other and 46.4% homology with A. victoria GFP, whereas the percent homology with A. victoria at the amino acid level was 31.1 and 28.4% for M. cavernosa and M. faveolata , respectively, and 82.7% with each other. Measurements of reflectance and of the excitation spectrum for chlorophyll fluorescence in GFP‐containing corals indicate that GFP absorption, emission, and reflection have negligible impact on the level of solar radiation reaching the zooxanthellae and therefore play no role in coral photosynthesis by either addition or removal of photons.

Field‐based measurements of oxygen uptake and swimming performance with adult Pacific salmon using a mobile respirometer swim tunnel - A. P. Farrell; C. G. Lee; K. Tierney; A. Hodaly; S. Clutterham; M. Healey; S. Hinch; A. Lotto (Journal of Fish Biology, 2003)
Novel field measurements of critical swimming speed ( U crit ) and oxygen uptake ( M o 2 ) in three species of adult Pacific salmon Oncorhynchus spp. up to 3·5 kg in body mass were made using two newly designed, mobile Brett‐type swim tunnel respirometers sited at a number of field locations in British Columbia, Canada. Measurements of U crit , which ranged from 1· 68 to 2·17 body lengths s −1 , and maximum M o 2 , which ranged from 8·74 to 12·63 mg O 2 kg −1 min −1 depending on the species and field location, were judged to be of similar quality when compared with available data for laboratory‐based studies. Therefore high quality respirometry studies were possible in the field using adult wild swimming salmonids. In addition, the recovery of wild adult Pacific salmon from the exhaustive U crit swim test was sufficiently rapid that swimming performance could be repeated with M o 2 being reestablished. This result suggests that wild adult salmon are capable of carrying a moderate excess post‐exercise oxygen consumption without adversely affecting U crit , maximum M o 2 or swimming economy. Such capabilities may be extremely important for timely migratory passages when salmonids face repetitive hydraulic challenges on their upstream migration.

Swimming patterns and behaviour of upriver-migrating adult pink (Oncorhynchus gorbuscha) and sockeye (O. nerka) salmon as assessed by EMG telemetry in the Fraser River, British Columbia, Canada - Scott G. Hinch; Emily M. Standen; Michael C. Healey; Anthony P. Farrell (Hydrobiologia, 2002)

In vitro cardiac performance in triploid brown trout at two acclimation temperatures - C. Mercier; M. Axelsson; N. Imbert; G. Claireaux; C. Lefrançois; J. Altimiras; A. P. Farrell (Journal of Fish Biology, 2002)
The maximum values for heart rate ( f H ), stroke volume ( V H ), cardiac output ( Q ) and myocardial power output, measured in vitro with a perfused heart preparation, as well as the isometric force‐frequency relationship for atrial and ventricular muscle strips, in triploid brown trout Salmo trutta were all comparable with established information for diploid rainbow trout Oncorhynchus mykiss . Therefore, it was concluded that triploidy is not associated with a major deficiency in maximum cardiac performance. However, a heightened sensitivity to ryanodine was discovered, which indicated an enhanced role for the sarcoplasmic reticulum in excitation‐contraction coupling in these triploid fish. It is suspected that the enhanced role of the ryanodine receptor may be a cellular compensation related to larger cardiac myocytes. It was also clearly established that there was a plateau in maximum cardiac performance between 14 and 18° C and this plateau might be a contributing factor to the reduced factorial aerobic scope and increased fish mortality observed at 18° C.

Cardiorespiratory status of triploid brown trout during swimming at two acclimation temperatures - J. Altimiras; M. Axelsoon; G. Claireaux; C. Lefrançois; C. Mercier; A. P. Farrell (Journal of Fish Biology, 2002)
At 14° C, standard metabolic rate (75·1 mg O 2 h −1 kg −1 ), routine metabolic rate (108.8 mg O 2 h −1 kg −1 ), active metabolic rate ( c . 380 mg O 2 h −1 kg −1 ), critical swimming speed (U crit 1·7 BL s −1 ), heart rate 47 min −1 ), dorsal aortic pressure (3·2 kPa) and ventilation frequency (63 min −1 ) for triploid brown trout Salmo trutta were within the ranges reported for diploid brown trout and other salmonids at the same temperature. During prolonged swimming ( c . 80% U crit ), cardiac output increased by 2·3‐fold due to increases in heart rate (1·8‐fold) and stroke volume (1·2‐fold). At 18° C, although standard and routine metabolic rates, as well as resting heart rate and ventilation frequency increased significantly, active metabolic rate and certain cardiorespiratory variables during exercise did not differ from those values for fish acclimated to 14° C. As a result, factorial metabolic scope was reduced (2·93‐fold at 18° C v . 5·13‐fold at 14° C). Therefore, it is concluded that cardiorespiratory performance in triploid brown trout was not unusual at 18° C, but that reduced factorial metabolic scope may be a contributing factor to the mortality observed in triploid brown trout at temperatures near 18° C.

Comparison of results from several AOGCMs for global and regional sea-level change 1900-2100 - J. M. Gregory; J. A. Church; G. J. Boer; K. W. Dixon; G. M. Flato; D. R. Jackett; J. A. Lowe; S. P. O'Farrell; E. Roeckner; G. L. Russell; R. J. Stouffer; M. Winton (Climate Dynamics, 2001)

Sulfur K-edge XANES study of local electronic structure in ternary monosulfide solid solution [(Fe, Co, Ni) 0.923 S] - S. P. Farrell; M. E. Fleet (Physics and Chemistry of Minerals, 2001)

A comparison of myocardial β-adrenoreceptor density and ligand binding affinity among selected teleost fishes - H. I. Olsson; N. Yee; H. A. Shiels; C. Brauner; A. P. Farrell (Journal of Comparative Physiology B, 2000)

Metal Analysis of Scales Taken from Arctic Grayling - A. P. Farrell; A. H. Hodaly; S. Wang (Archives of Environmental Contamination and Toxicology, 2000)

Gastrointestinal blood flow in the red Irish lord, Hemilepidotus hemilepidotus : long-term effects of feeding and adrenergic control - M. Axelsson; H. Thorarensen; A. P. (Tony) Farrell; S. Nilsson (Journal of Comparative Physiology B, 2000)

A Study of the Lethal and Sublethal Toxicity of Polyphase P-100, an Antisapstain Fungicide Containing 3-Iodo-2-Propynyl Butyl Carbamate (IPBC), on Fish and Aquatic Invertebrates - A. P. Farrell; E. Stockner; C. J. Kennedy (Archives of Environmental Contamination and Toxicology, 2000)

A Study of the Lethal and Sublethal Toxicity of Polyphase P-100, an Antisapstain Fungicide Containing 3-Iodo-2-Propynyl Butyl Carbamate (IPBC), on Fish and Aquatic Invertebrates - A. P. Farrell; E. Stockner; C. J. Kennedy (Archives of Environmental Contamination and Toxicology, 1998)

Influence of earthworms on soil properties and grass production in reclaimed cutover peat - K. E. Boyle; J. P. Curry; E. P. Farrell (Biology and Fertility of Soils, 1997)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)